Thermal stress resistance and aging effects of Panax notoginseng polysaccharides on Caenorhabditis elegans - Feng, Shiling; Cheng, Haoran; Xu, Zhou; Shen, Shian; Yuan, Ming; Liu, Jing; Ding, Chunbang (International journal of biological macromolecules, 2015)
Panax notoginseng attract public attention due to their potential biomedical properties and corresponding health benefits. The present study investigated the anti-aging and thermal stress resistance effects of polysaccharides from P. notoginseng on Caenorhabditis elegans. Results showed polysaccharides had little scavenging ability of reactive oxygen species (ROS) in vitro, but significantly extended lifespan of C. elegans, especially the main root polysaccharide (MRP) which prolongs the mean lifespan of wild type worms by 21%. Further study demonstrated that the heat stress resistance effect of polysaccharides on C. elegans might be attributed to the elevation of antioxidant enzyme activities (both superoxide dismutase (SOD) and catalase (CAT)) and the reduction lipid peroxidation of malondialdehyde (MDA) level. Taken together, the results provided a scientific basis for the further exploitation of the mechanism of longer lifespan controlled by P. notoginseng polysaccharides on C. elegans. The P. notoginseng polysaccharides might be considered as a potential source to delay aging.
Gesehen am 03.08.2020